Effectiveness of the KOKAMI (Mysterious Box and Card) Learning Media in Enhancing Student Engagement and Mastery of Volleyball Concepts in Senior High School Education - Maslikan Maslikan (INSPIRETECH GLOBAL INSIGHT, 2026)
The learning process constitutes the core activity that determines the success or failure of achieving educational objectives, as it directly shapes students’ cognitive, affective, and psychomotor development. Therefore, teachers are required to demonstrate creativity in selecting and designing instructional methods and media that effectively support classroom learning. Innovation in learning media is essential to attract students’ attention and enhance their motivation, particularly in subjects that demand active engagement such as physical education. In Indonesian high schools, sports science is a compulsory subject for students in science and social science tracks, emphasizing the development of physical fitness, conceptual understanding, and healthy lifestyle habits. Volleyball, as one of the core topics taught in Grade XII under Curriculum 2013, involves abstract and memorization-based content that often requires deeper conceptual comprehension. To address these challenges, teachers may integrate interactive learning media to create an engaging classroom atmosphere and facilitate active participation. This study introduces the mysterious box and card (KOKAMI) learning media as an instructional innovation aimed at enhancing student engagement in volleyball learning. KOKAMI consists of cards containing materials, questions, images, commands, bonuses, or sanctions, placed inside envelopes and further inserted into a concealed box, making the learning process more stimulating and unpredictable. Through this mechanism, students are encouraged to think innovatively, creatively, and critically, while actively participating in classroom activities. The implementation of KOKAMI was carried out with Grade XII MIPA 1 students of SMA Negeri 2 Pekanbaru. Findings indicate a substantial improvement in student learning activity, increasing from an average of 72.53% in Cycle I to 88.82% in Cycle II. Learning mastery also demonstrated significant progress, rising from 89.47% in Cycle I to 100% in Cycle II. These results suggest that KOKAMI is an effective media innovation for promoting active participation, improving conceptual understanding, and enhancing learning outcomes in volleyball instruction within high school physical education.